Atom‐Economic Electron Donors for Photobiocatalytic Halogenations. Issue 18 (25th July 2018) - Seel, Catharina Julia; Králík, Antonín; Hacker, Melanie; Frank, Annika; König, Burkhard; Gulder, Tanja
Abstract: In vitro cofactor supply and regeneration have been a major obstacle for biocatalytic processes, in particular on a large scale. Peroxidases often suffer from inactivation by their oxidative co‐factor. Combining photocatalysis and biocatalysis offers an innovative solution to this problem, but lacks atom economy due to the sacrificial electron donors needed. Herein, we show that redox‐active buffers or even water alone can serve as efficient, biocompatible electron sources, when combined with photocatalysis. Mechanistic investigations revealed first insights into the possibilities and limitations of this approach and allowed adjusting the reaction conditions to the specific needs of biocatalytic transformations. Proof‐of‐concept for the applicability of this photobiocatalytic reaction setup was given by enzymatic halogenations. Abstract : Photo meets bio : Photobiocatalysis constitutes an elegant way to overcome the pending problem of cofactor inactivation in peroxidase catalyzed transformations. In this context, the utility of redox‐active buffers or even water alone as efficient, biocompatible electron sources has been demonstrated by combining photocatalytic in situ H2 O2 generation with enzymatic halogenations.